Analysis of Consumers Satisfaction and Jackfruit Chips Quality Improvement Strategy Using integration Quality Function Deployment (QFD) withAnalytical Hierarchy Process (AHP) (a Case Study in CV. Aneka Rasa, Malang) - Andan Linggar Rucitra; Imam Santoso; Retno Astuti (The Indonesian Green Technology Journal, 2014)
The development of local food products very rapidly at this time is marked by the emergence of a variety of brands on the market. CV Aneka Rasa is a business unit that manufactures special food products of Malang with the average sales per month jackfruit chips in 2013 amounted to 97.5 kg judged more dominant than the consumers preferred other fruit crisps. Quality Function Deployment (QFD) is an effective tool that can help companies towards improving processes to meet consumer expectations. The use of QFD method needs to be integrated with other methods for obtaining the order of priority of an issue, the proper method in analyzing customer satisfaction that QFD is suitable to be integrated with AHP method. The purpose of this study was to analyze the attributes of desire and customer satisfaction with jackfruit chips Aneka Rasa and to formulate strategies to improve product quality jackfruit chips Aneka Rasa. The result of this study was that the sense of a constant volume of jackfruit chips on the tops with the value of 7.5. The highest priority of technical responses that allow recording to the CV. Aneka Rasa was the determination of the appropriate selling price with the value of 0.383. Keywords: customer satisfaction, quality improvement, QFD, AHP